Evolution of the “American Dream” as a Value System and its Representation in Hollywood Movies - Melkumyan, Yuliana; Mkrtchyan, Seda (Journal of Sociology: Bulletin of Yerevan University, 2023)
The “American dream” is a value system, which is the locomotive of the development of American society. It is one of the core elements of the American identity. The idea of the “American dream” presents the terminal values of equality, liberty, prosperity and happiness. Hard work, sacrifice, courage in the face of taking risks, diligence and the act of overcoming hardships are presented as instrumental values, which are required to achieve the terminal values mentioned above. The concept of the “American Dream” has evolved with the passage of time and faced different challenges, which resulted in a number of contradictions between the dream and the social reality. Hollywood movies are used as one of the tools to propagate the “American Dream” both inside of the United States and abroad. This article examines the representation of the terminal and instrumental values of the “American Dream” in Hollywood films (2018-2021) with anti-racist content, as well as films about family, the American Armed Forces, the US president, and the rule of law, through visual, verbal and audio means. Nevertheless, while the films communicate the same terminal and instrumental values, they also occasionally show the existing contradictions. Hard work does not always lead to achieving the "American dream". Even though the fight for equality is going strong, inequality still exists. Along with the rule of law, there are also manifestations of corruption. At the same time, the USA continues to be presented as a safe, powerful and wealthy country.
Keywords: “American Dream”; value system; terminal values; instrumental values; propaganda; communication; Hollywood movies